Can probiotics mitigate age-related neuroinflammation leading to improved cognitive outcomes? - Anderson, R. C. (Frontiers in Nutrition, 2022)
Changes in brain structure and cognitive function are a natural part of ageing; however, in some cases these changes are more severe resulting in mild cognitive impairment (MCI) or Alzheimer’s disease (AD). Evidence is mounting to show that neuroinflammation is an underlying risk factor for neurodegenerative disease progression. Age-related neuroinflammation does not appear to occur in isolation and is part of increased systemic inflammation, which may in turn be triggered by changes in the gut associated with ageing. These include an increase in gut permeability, which allows immune triggering compounds into the body, and alterations in gut microbiota composition leading to dysbiosis. It therefore follows that, treatments that can maintain healthy gut function may reduce inflammation and protect against, or improve, symptoms of age-associated neurodegeneration. The aim of this mini review was to evaluate whether probiotics could be used for this purpose. The analysis concluded that there is preliminary evidence to suggest that specific probiotics may improve cognitive function, particularly in those with MCI; however, this is not yet convincing and larger, multilocation, studies focus on the effects of probiotics alone are required. In addition, studies that combine assessment of cognition alongside analysis of inflammatory biomarkers and gut function are needed. Immense gains could be made to the quality of life of the ageing population should the hypothesis be proven to be correct.